Understanding system innovation adoption: A comparative analysis of integrated soil fertility management uptake in Tamale (Ghana) and Kakamega (Kenya) - Adolwa, Ivan S.; Schwarze, Stefan; Waswa, Boaz Shaban; Buerkert, Andreas (Cambridge University Press, 2019)
Sustainable intensification of African farming systems has been high on the agenda of research and development programs for decades. System innovations such as integrated soil fertility management (ISFM) and conservation agriculture have been proposed to tackle the complex challenges farmers face. In this study, we assess how different factors at the plot, farm and institutional level can influence the adoption of ISFM. We employed a stratified sampling approach to randomly select 285 and 300 farmers in Tamale, northern Ghana and Kakamega County, western Kenya, respectively. These two locations were selected to understand the underlying reasons for their divergent adoption levels. Ordinal regression models were used to identify determinants of adoption. In Tamale, adoption rates of ISFM are much lower than in Kakamega. Only 3% of the farmers fully adopted the recommended practices compared with 36% in Kakamega. The low availability of improved seeds is a major reason for the lower uptake of the complete ISFM paradigm in Tamale. The econometric analysis revealed that plot level variables such as soil carbon, soil texture, slope and plot area had a significant effect on the number of adopted ISFM components at both locations. Moreover, family labor availability is also an important factor. Other farm and household characteristics, such as off-farm occupation, livestock ownership, and membership in associations, matter for Kakamega only. Key policy recommendations include promotion of locally available organic resources and improved access to improved seeds in Tamale.